The moderating role of resilience in the relationship between marital stress and depression - Enugu State University; NzekweIfeoma Maryrose; Madike, Eunice Nwabugo; Nwatu, A. C.; Ugwu, Chika Gloria; Douglas, John Ufuoma; Omeje, Obiageli; Ekwo Jude Chukwudi; Anike, Raphael Ugwu; Eze, Boris Ejike (International Journal of Educational Excellence and Innovation, 2024)
The study investigated the moderating role of resilience in the relationship between marital stress and depression among married teachers, with one hundred thirty-five (135) married teachers that comprises of 102 females and 33 males with an age mean of 32.20 and S.D 3.81 selected as participants using multi-stage (cluster, simple: balloting, and purposive) sampling techniques. Zung (1965) Self-rating Depression Scale (SDS), Omoluabi (1994) marital stress Inventory (MSI) and Connor and Davidson (2003). Connor-Davidson Resilience Scale (CD-RISC) were used for data collection, a cross-sectional survey design was adopted, while a moderated hierarchical multiple regression was used for data analysis. The finding shows that marital stress St= .551*** and t= 7.608*** at p< .001 positively predicted depression, Resilience St= -.517*** and t= -6.962*** at p< .001 negatively predicted depression among school teachers and Resilience St= -.748***and t= -7.178*** at p< .001 negatively moderated the relationship between marital stress and depression. Hence, school management can consider hiring psychologists to work with teachers to improve their resilience or educate them on the importance of resilience in managing depression.